Observations of ELF Signal and Noise Variability on Northern Latitude Paths. - Davis,John R.; Meyers,William D. (1975)
Extremely-low-frequency (ELF) signal and noise data from a network of receiving sites in the North Atlantic region are reported for propagation tests that were conducted in 1974 and early 1975. Statistics of the signal and noise behavior indicate that variability introduced by geophysical phenomena in the ionosphere are of significance and that this variability exists to some degree even under seemingly quiet conditions. A correspondence is observed between periods of unusually disturbed ELF propagation and geomagnetic activity, indicating that charged particles precipitated from the magnetosphere following solar eruptions are responsible for the propagation variability. (Author)